Tools and Methods for Developing Logical Thinking in Students in the Economic Sphere (Uzbekistan Open Conference, 2025)
This article emphasizes the importance of logical thinking in the modern world and the conditions created for its development. It examines external factors influencing the formation of students’ logical thinking skills and presents a number of methods for their development. In addition, approaches to fostering young people’s creative thinking abilities are discussed. Various methods and conclusions related to the educational process are presented to promote the development of logical and creative thinking.